(untitled) (Research, Society and Development, 2021)
The aim of this cross-sectional study was to assess the impact of temporomandibular disorder (TMD) on oral health-related quality of life (OHRQoL) of adolescents. The OHRQoL of adolescents undergoing dental treatment at a University clinic in 2019 was measured using the Brazilian version of the Oral Heath Impact Profile – 14 (OHIP-14). The diagnosis of TMD was performed using Research Diagnostic Criteria for Temporomandibular disorders (RDC/TMD). The patients were examined for other oral conditions and the parents/guardians answered questions addressing socioeconomic/demographic characteristics and the general health of the adolescents. Statistical analysis involves simple and multiple logistic regression models. Ninety male and female adolescents between 13 and 18 years of age participated in the study. The prevalence of negative impact on OHRQoL was 34%. In the unadjusted analysis, negative impact on OHRQoL was associated with a poorer self- perception of general and oral health of the adolescent, nonspecific symptoms including pain, and generalized anxiety disorder, caries, reports of dental pain, muscle disorders and disc displacement, and chronic pain related to TMD. In the adjusted model, negative impact on OHRQoL was associated with all diagnoses related to TMD on the RDC/TMD, except signs of depression. Adolescents with at least one diagnosis related to TMD were 4.13-fold more likely (95% CI:1.08-15.80) to have negative impact on OHRQoL than adolescents without a diagnosis of TMD. The different diagnostic categories of TMD had a negative impact on the OHRQoL of the adolescents analyzed in the present study.